Classroom Activities to Promote Students' Literacy Development - rizqiani, diyah ayu (J-SHMIC : Journal of English for Academic, 2017)
Literacy leads students to academic success. The power of literacy does not only lie in the person’s ability to read and write, but also in the person’s capacity to apply these skills effectively for connecting, interpreting, and discerning the intricacies of the world. The purpose of this study was to describe various learning activities in grade one Ellipse Class. The study was descriptive, in which the researcher described the phenomena in the setting without attempting to make inferences or causal statements. The study was conducted at Budi Mulia Dua Pandeansari Elementary School in Yogyakarta. The instruments of this study were observation sheets, documentations, and interview protocols.  The participants of this study were ten students and two classroom teachers of Ellipse Class. The results show that there are interactive activities which are able to promote students’ literacy development such as reading activities, diary writing, project-based activities, and story writing.   Literasi mendorong kesuksesan akademis siswa. Kekuatan literasi tidak hanya terletak pada kemampuan sesesorang untuk membaca dan menulis, tetapi juga terletak pada kemampuan seseorang untuk menggunakan ketrampilan-ketrampilan ini secara efektif untuk menghubungkan, menginterpretasikan, dan mengurai kerumitan dunia. Tujuan penelitian ini adalah untuk menggambarkan berbagai kegiatan di kelas yang dilaksanakan di Kelas Satu Ellipse. Penelitian ini merupakan penelitian deskriptif, peneliti mendeskripsikan fenomena di lapangan tanpa berusaha mencampuri fakta yang terjadi di lapangan. Penelitian ini diadakan di SD Budi Mulia Dua Pandeansari Yogyakarta. Dalam penelitian ini, peneliti menggunakan berbagai instrumen diantaranya lembar observasi, dokumentasi, dan pedoman wawancara. Subjek penelitian ini adalah sepuluh siswa kelas satu Kelas Ellipse. Hasil penelitian menunjukkan bahwa ditemukan berbagai kegiatan interaktif di kelas yang dapat menunjang perkembangan literasi siswa diantaranya kegiatan membaca, menulis buku harian, kegiatan berbasis projek, dan kegiatan menulis cerita.